Currency substitution, portfolio diversification and money demand - Freitas, Miguel Lebre de (2004)
We extend the Thomas (1985) dynamic optimissing model of money demand and currency substitution to the case in which the individual has no access to bonds denominated in foreign currency. We show that in this case the demand for domestic money is influenced by portfolio decisions. Contrary to what defended by the Portfolio Balance Approach to currency substitution, the results obtained in this paper suggest that the significance of an expected exchange rate depreciation term in the demand for domestic money provides a valid test for the present of curency substitution. The results also suggest that, in countries facing monetary instability and currency substitution, restricting the availability of interest-bearning assets denominated in foreign currency may have a destabilising impact on the money demand.